Pengaruh Kepemimpinan, Fasilitas, dan Teknologi Terhadap Kinerja Karyawan Perusahaan Kontraktor: The Influence of Leadership, Facility, and Technology on Construction Employee Performance - Setiabudi, Muhammad Lutfi; Kirana, Kusuma Candra; Wiyono, Gendro (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Construction industry is a complex system as a main driving force of the economy. In such a complex system, the excellent performance of all components of the construction company system is a must to achieve the project's success goals. The link between employee performance and the availability of facilities, the use of technology, and appropriate leadership has become the concern of researchers in human resources because these three factors are crucial in increasing employee productivity. This research is a cross-sectional study to determine the influence of leadership, facilities, and technology on the performance of contractor company employees at Putera Jaya Andalan Co. Data collection was carried out by direct observation and questionnaires, which were then analyzed using the T-test to path analysis. The results of this study indicate that applying the right leadership style, work facilities, and technology in the company can positively and significantly impact employee performance. The better the leadership style, work facilities, and technology, the better the performance of employees. Keywords: construction industry, employee performance, Putera Jaya Andalan, availability of facilities, the use of technology